The Interaction Between Stock Dynamics, Fishing and Climate Caused the Collapse of the Jack Mackerel Stock at Humboldt Current Ecosystem - Lima, Mauricio; Canales, T. Mariella; Wiff, Rodrigo; Montero, José (Frontiers in Marine Science, 2020)
The collapse of marine fisheries had caused a cascade of ecological, social and economic consequences. Recognizing the complex nature of the fisheries collapses is essential for understanding the impact of human activities on natural systems. The rapid and abrupt shifts in abundance exhibited by some marine fish populations can be driven by the fishing fleet behaving like generalist predators. Here, we propose that fishing fleet has a s-shaped functional predator function that, combined with economic factors and ENSO variability could cause rapid and abrupt transitions in the of jack mackerel (Trachurus murphyi) fishery in the south-eastern Pacific. Our results showed that fishing fleet predator functional response is well described by a s-shaped function, where ENSO variability (El Niño/La Niña years) appears to decrease/increase the fishing rate. Our model predictions were able to accurately forecast independent data of jack-mackerel acoustic survey estimates. We show that the population trend and collapse of jack mackerel stock at the Humboldt Current Ecosystem (HCE) can be explained by the changes in fishing effort, which seem to be driven by economic forces and El Niño climatic variability. Our simple model allows us to explore some management responses in a heuristic manner. The most critical element seems to be the combination of an n-shaped isocline for fish stock growth, modulated by ENSO variability, and a horizontal isocline of fishing effort which is highly sensitive to changes in the profitability of the fishery. Therefore, the implementation of management policies based on simple theoretical models will be increasingly required to harvest fish stocks in these times of growing demographic demands and climate change.